Expanding the Phenotype and Genetic Defects Associated with the GOSR2 Gene. Issue 3 (17th June 2015) - Praschberger, Roman; Balint, Bettina; Mencacci, Niccolo E.; Hersheson, Joshua; Rubio‐Agusti, Ignacio; Kullmann, Dimitri M.; Bettencourt, Conceição; Bhatia, Kailash; Houlden, Henry
Abstract: Background: The homozygous missense mutation c.430G>T (p.G144W) in the GOSR2 gene has been repeatedly shown to cause progressive myoclonus epilepsy/ataxia. Thus far, no other disease associated GOSR2 mutation has been reported. Methods: From epilepsy, movement disorder and genetic clinics 43 patients suffering from progressive myoclonus epilepsy/ataxia were screened for defects in GOSR2, SCARB2 and CSTB . Results: A 61‐year‐old female patient suffering from progressive myoclonus epilepsy was found to be compound heterozygous for the known c.430G>T and a novel c.491_493delAGA (p.K164del) GOSR2 mutation. This is so far the oldest GOSR2 patient and her disease course seems overall milder. Conclusions: This finding further highlights the GOSR2 gene as a cause of progressive myoclonus epilepsy and expands the genotype for a potentially weaker disease allele.